Contemporary Classics? The Early Onset of Influence of Articles Published in Criminology and Criminal Justice Journals, 2010–2015. Issue 3 (3rd July 2019) - Graham, Amanda; Pratt, Travis C.; Lee, Heejin; Cullen, Francis T.
Abstract: Citation analysis is a valuable method for tracking the growth and transmission of scientific knowledge. In criminology and criminal justice, such analyses tend to be focused on "classic" works or on highly cited scholars over many years. As an alternative approach, we focus on work that has been cited rather quickly – what we term the "early onset" of impact. In doing so, we identified 221 of the most highly cited peer-reviewed articles, authored by 480 scholars, which were published in criminology and criminal justice journals between 2010 and 2015. Analyses reveal wide variation in substantive topics and methodological approaches, as well as a substantial gender gap with respect to authorship. Additional analyses provide insight into both journal and institutional/program prestige. We conclude with directions for future research and stress the importance of tracking over time articles that appear to be off to an early start with respect to scholarly impact.